2017
DOI: 10.3354/meps11990
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface algal blooms of the northwestern Arabian Sea

Abstract: ABSTRACT:In situ plankton sampling, combined with remotely sensed and ocean Seaglider observations, provided insight into the termination of the winter monsoon bloom and subsequent evolution into a subsurface fluorescence maximum in the northwestern Arabian Sea. This subsurface maximum gradually descended, presenting increased fluorescence between 25 and 55 m depth during the spring inter-monsoon season. Species diversity decreased by half within the deep fluorescence maximum relative to the bloom. The dinofla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Additionally, seasonal changes (i.e. increase of temperature from March to June) have affected vertical profiles of the physical and biological parameters (Piontkovski et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, seasonal changes (i.e. increase of temperature from March to June) have affected vertical profiles of the physical and biological parameters (Piontkovski et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 712 dives with 1424 vertical profiles of environmental parameters covering over 2080 km and repeating the survey transects 24 times out over a period of 91 days were carried out. The ocean glider was equipped with a Seabird free-flushing CT sail, an Aanderaa 4330F oxygen optode, a Biospherical QSP-2150 PAR sensor (spectral region -400-700 nm), a Wetlabs Triplet ECO sensor measuring chlorophyll a (based on fluorescence intensity) and backscatter at 470 and 700 nm (Piontkovski et al 2017). Satellite communication was used for retrieval of the data in near real time after every dive at a speed of about 25 cm s -1 .…”
Section: Ocean Glider's Deploymentmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, prior to their appearance as surface blooms, Noctiluca were observed in large numbers at depth in association with the oxycline (Goes & Gomes, 2016). In their study, Piontkovski et al (2017) were able to show a gradual descent of Noctiluca cells into the water column towards the oxycline following peak blooms at the surface. More recently based on observations that showed that Noctiluca blooms of the eastern Arabian Sea were not associated with hypoxic waters Lotliker et al (2018) argued that low oxygen waters were not the cause of Noctiluca blooms.…”
Section: Noctiluca Bloomsmentioning
confidence: 90%